Using IMAGE Model to De-Center Stereotypes in EFL Colombian Eighth Graders - Ana María Sagre-Barboza; Paula Andrea García-Montes; Sobeida del Carmen Correa-Morelo (HOW)
This article informs the results of a study conducted at a public secondary school in Colombia whose purpose was to explore how eighth-grade students dispel judgment and stereotypes concerning cultural differences through authentic materials inserted in the IMAGE model. The research design involved a qualitative research method and the application of the action research cycle. The qualitative data were analyzed using deductive coding considering students’ three preconceived stereotypes. The results reveal that students could move from generalizing and having prejudices to being more mindful of cultural differences concerning the English language. Likewise, this study shows that the target language, grammar, culture, and content could be integrated into a single English class.